KEMAMPUAN MULTIPEL REPRESENTASI MATEMATIS MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK (PMR) PADA MATERI PECAHAN - Wahid Umar; Pamuti Pamuti (Universitas Khairun, 2022)
This research is focused on elementary school students multiple mathematical representations through realistic mathematics education on fractions lesson. The problem that will be solved is